Low IL-6, IL-10, and TNF-α and High IL-13 Cytokine Levels Are Associated with Severe Hepatic Fibrosis in Schistosoma mansoni Chronically Exposed Individuals - Mable M. Mutengo; Takafira Mduluza; Paul Kelly; James C. L. Mwansa; Geoffrey Kwenda; Patrick Musonda; James Chipeta (Journal of Parasitology Research)
Several studies have attributed the etiopathogenesis of chronic Schistosoma mansoni related hepatic fibrosis to unregulated immune responses against trapped parasite ova in the host. However, there is limited data on immune profiles associated with varying degrees of the disease in a population under chronic exposure to the parasite. We therefore investigated the role of selected T-helper (Th)1, Th2, and Th17 cytokines in relation to hepatic fibrosis severity among individuals resident in a hyper-Schistosoma mansoni endemic region of Western Zambia. Two hundred and forty-four S. mansoni infected individuals with and without fibrosis were analysed for cytokine profiles. Based on hepatic fibrosis stage as determined by ultrasound, participants were categorized into Group 0, Group I, Group II, and Group III. Cytokines were measured in S. mansoni egg stimulated whole blood culture supernatants using the BD Cytometric Bead Array kits. Compared to the nonfibrotic group, participants in the severe hepatic fibrotic group produced less interleukin- (IL-) 6, IL-10, and tumour necrosis factor-alpha (TNF-α). On the other hand, IL-13 was significantly elevated in this group compared to the nonfibrotic group (p<0.001). Our results suggest that low IL-6, IL-10, and TNF-α and high IL-13 levels may influence S. mansoni disease progression.